Introduction to the Best-Case/Worst-Case Framework Within Transplantation Surgery to Improve Decision-Making for Increased Risk Donor Organ Offers. (December 2020) - Highet, Alexandra; Cassidy, Devon E.; Gomez-Rexrode, Amalia E.; Kirsch, Michael J.; Eton, Ryan; Brown, Craig S.; Waits, Seth A.; Englesbe, Michael J.
Public Health Service increased risk donor kidneys are discarded 50% more often than nonincreased risk donor kidneys despite equivalent patient and graft survival outcomes. Patient and provider biases as well as challenges in risk interpretation contribute to the underuse of increased risk donor organs. As the ultimate decision to accept or reject an increased risk donor organ results from the patient–provider conversation, there is an opportunity to improve this dialogue. This report introduces the best-case/worst-case communication guide for structuring high-stake conversations on increased risk kidney offers between transplant providers and their patients. Through best case/worst case, providers focus on eliciting patient values and long-term goals. The patient's unique context can then inform an individualized discussion of "best, " "worst, " and "most likely" outcomes and support the provider's ultimate recommendation. Transplant providers are encouraged to adopt this communication strategy to enhance shared decision-making and improve patient outcomes.